Perception of the learning climate and its prediction of wellbeing in psychology students at a Chilean university - Cobo-Rendón, Rubia; García-Álvarez, Diego; Rendon, Ramón Cobo; Santana, Javiera (Frontiers in Education, 2024)
Autonomy-supportive environments have been identified as predictors of students’ wellbeing and engagement. This paper aimed to examine the perception of learning climate and its predictive ability in the multidimensional wellbeing of university students. An associative and predictive approach was adopted, carried out through a cross-sectional study that included 295 students from a Chilean university. Participants completed a learning climate questionnaire and the PERMA-Profiler. Results indicated that students reported moderately high levels of wellbeing in general, with the dimensions of positive relationships, engagement, and purpose showing the highest scores. Regarding learning climate, responses indicated a mostly positive perception, with scores above the midpoint on the scale. No significant differences were found in wellbeing or perception of learning climate according to academic year. However, a significant interaction effect between gender and learning climate was found for overall multidimensional wellbeing, F(1, 286) = 4.67, p = 0.032, η2 = 0.016. Men in the high learning climate group showed higher wellbeing than women, while women in the low climate group outperformed men in the same group. Additionally, significant gender differences were observed in the engagement dimension, F(1, 286) = 11.23, p < 0.001, η2 = 0.033, with men in the high learning climate group reporting higher engagement, and women in the low learning climate group showing higher engagement than their male counterparts. Perception of learning climate explained a significant amount of the variance in all dimensions of wellbeing. These findings highlight the importance of promoting learning environments that foster autonomy and teacher support, and suggest that the learning climate may have different impacts on wellbeing depending on gender.